Parasynnemellisia khasiana gen. et sp. nov. (Phaeosphaeriaceae, Pleosporales), on bamboo litter, from Meghalaya, India - Pratibha, J.; Bhat, D. Jayarama; Dawoud, Turki M.; Ashish, Prabhugaonkar (Phytotaxa, 2025)
Parasynnemellisia khasiana gen. et sp. nov., occurring on dead and decaying culms of a bamboo, Chimonocalamus griffithianus (Poaceae), collected from Mawsynram, Meghalaya, India, is described and illustrated. The fungus is characterized by synnematous, moniliaceous conidiomata, monophialidic conidiogenous cells and hyaline, lanceolate, navicular, aseptate, smooth, slimy conidia. Analyses of partial ITS and LSU sequences data, place the taxon close to genus Setophoma with very low bootstrap support within the family Phaeosphaeriaceae in order Pleosporales. Genus Setophoma morphologically differs being pycnidial fungus.